Philosophy and Social Sciences in a Securitological Perspective - Janusz Świniarski (Polish Political Science Yearbook, 2023)
The inspiration of this text is the belief of the Pythagoreans that the roots and source of complete knowledge is the quadruple expressed in the “arch-four”, also called as tetractys. Hence the hypothesis considered in this paper is: the basis of the philosophy of social sciences is entangled in these four valours, manifested in what is “general and necessary” (scientific) in social life, the first and universal as to the “principles and causes” of this life (theoretically philosophical) and “which can be different in it” (practically philosophical) and “intuitive”. The quadruple appears with different clarity in the history of human thought, which seeks clarification and understanding of the things being cognised, including such a thing as society. It is exposed in the oath of the Pythagoreans, the writings of Plato and Aristotle, who applied these four valours, among other things, in distinguishing the four types of knowledge and learning about the first four causes and principles. This fourfold division seems to be experiencing a renaissance in contemporary theological-cognitive holism and can be treated as an expressive, a “hard core”, and the basis of research not only of social but mainly of global society as a social system. This entanglement of the foundations of the philosophy of the social sciences leads to the suggestion of defining this philosophy as the knowledge of social being composed of “what is general and necessary” (scientific), genetically first, universal (theoretically philosophical) and “being able to be different” (philosophically practical) and intuitive.